Development of the Acute Coronary Syndrome Predictive Scale - Shahla Elyaszadeh; Sevda Gardashkhani; Mehdi Heidarzadeh (Journal of Caring Sciences)
Introduction: The use of a predictive scale for acute coronary syndrome (ACS) can play an essential role in screening high-risk individuals. This study aimed to develop the ACS predictive scale (ACS-PS) and investigate its construct validity, reliability, sensitivity and specificity. Methods: This was a retrospective methodological study with the aim of developing a predictive scale for ACS in Iran in 2019. In this study, the content validity (content validity index [CVI] and content validity ratio [CVR]), construct validity, sensitivity, specificity, cutoff point and internal consistency of the 13-item scale for predicting ACS (in Persian) were investigated. Participants included patients with a definite diagnosis of ACS (n=150) and a healthy group without ACS (n=143). Results: The score range of the 13-item scale was 0-130, and with a cutoff point of 11.5, both the sensitivity and specificity of the scale were 0.75. Cronbach’s alpha coefficient was 0.80. Conclusion: The present study introduced a sensitive and specific scale for predicting ACS. The ACS-PS is a partially short-form scale and requires less time to complete.